Folic Acid Self-Assembly Enabling Manganese Single-Atom Electrocatalyst for Selective Nitrogen Reduction to Ammonia - Wang, Xuewan; Wu, Dan; Liu, Suyun; Zhang, Jiujun; Fu, Xian‑Zhu; Luo, Jing‑Li (Nano-Micro Letters, 2021)
Efficient and robust single-atom catalysts (SACs) based on cheap and earth-abundant elements are highly desirable for electrochemical reduction of nitrogen to ammonia (NRR) under ambient conditions. Herein, for the first time, a Mn–N–C SAC consisting of isolated manganese atomic sites on ultrathin carbon nanosheets is developed via a template-free folic acid self-assembly strategy. The spontaneous molecular partial dissociation enables a facile fabrication process without being plagued by metal atom aggregation. Thanks to well-exposed atomic Mn active sites anchored on two-dimensional conductive carbon matrix, the catalyst exhibits excellent activity for NRR with high activity and selectivity, achieving a high Faradaic efficiency of 32.02% for ammonia synthesis at − 0.45 V versus reversible hydrogen electrode. Density functional theory calculations unveil the crucial role of atomic Mn sites in promoting N2 adsorption, activation and selective reduction to NH3 by the distal mechanism. This work provides a simple synthesis process for Mn–N–C SAC and a good platform for understanding the structure-activity relationship of atomic Mn sites. Highlights: 1 A manganese single-atom catalyst is developed via a facile folic acid self-assembly strategy. 2 The catalyst exhibits outstanding activity and selectivity for electrochemical reduction of nitrogen to ammonia (NRR). 3 Electrocatalytic mechanism of Mn–N3 site for NRR is unveiled by a combination of experimental and computational study.